Downregulation of lysyl oxidase in venous malformations: Association with vascular destabilization and sclerotherapy. Issue 5 (11th March 2020) - Zhu, Junyi; Shao, Ming; Guo, Fengyuan; Ren, Jiangang; Tang, Zirong; Geng, Jinhuan; Xu, Zhi; Jia, Jun; Chen, Lili; Jia, Yulin
Abstract: Venous malformations (VM) are localized defects in vascular morphogenesis manifested by dilated venous channels with reduced perivascular cell coverage. As a vital enzyme for extracellular matrix (ECM) deposition, lysyl oxidase (LOX) plays important roles in vascular development and diseases. However, the expression and significance of LOX are unknown in VM. Herein, 22 VM specimens and eight samples of normal skin tissues were evaluated immunohistochemically for the expression of LOX, α‐smooth muscle cell actin (α‐SMA) and transforming growth factor‐β (TGF‐β). In vitro studies on human umbilical vein endothelial cells (HUVEC) were employed for determining potential mechanisms. Our results showed that LOX expression was significantly reduced in VM compared with normal skin tissues, in parallel with attenuated perivascular α‐SMA + cell coverage and TGF‐β downregulation in VM. Further correlation analysis indicated that LOX expression was positively correlated with perivascular α‐SMA + cell coverage and TGF‐β expression in VM. Moreover, marked elevation of LOX, TGF‐β and α‐SMA was observed in bleomycin‐treated VM samples. Furthermore, our in vitro data demonstrated that both recombinant TGF‐β and bleomycin induced obvious increase of LOX expression and activity and a concomitant increase in ECM components in HUVEC, which could be reversed by LOX inhibition. To our best knowledge, this study revealed for the first time the downregulation of LOX in VM and its correlation with vascular destabilization and TGF‐β‐induced endothelial ECM deposition. Moreover, our results highlighted that LOX may be implicated in the sclerotherapy of VM and holds promise as a therapeutic target.